Salicylate-induced increases in free triiodothyronine in human serum: Evidence of inhibition of triiodothyronine binding to thyroxine-binding globulin and thyroxine-binding prealbumin - Larsen, P. R. (1972)
Addition of sodium salicylate to human serum at concentrations often obtained during aspirin therapy causes 100-200% increases in free triiodothyronine (T(3)) and free thyroxine (T(4)) as estimated by ultrafiltration. The increase in free T(3) was unexpected since previous data had suggested that salicylate inhibits binding of T(4) only to thyroxine-binding prealbumin (TBPA) and that T(3) is not bound to this protein. Using ultrafiltration techniques, we demonstrated binding of T(3) to TBPA. The affinity constant for T(3)-TBPA binding appears to be slightly greater than that for albumin-T(3) binding. While salicylate inhibits the binding of T(3) (and T(4)) to TBPA, it can be predicted that little change will be observed in the free T(3) (or free T(4)) without inhibition of thyroid hormone binding to thyroxine-binding globulin (TBG). Using a competitive-binding protein displacement technique, it has been shown that sodium salicylate, like diphenylhydantoin (DPH), inhibits the binding of T(3) and T(4) to TBG. The magnitude of the increase in free T(3) and free T(4) induced by salicylates suggests that interference with TBG binding is its major effect. Aspirin was administered orally to two normal subjects in quantities sufficient to obtain serum salicylate levels of 20-25 mg/100 ml. This resulted in a decrease of 20-30% in total serum T(3) and T(4) levels. This decrease in T(4) levels is similar in magnitude to that previously observed in subjects receiving DPH. Unlike what has been observed with DPH treatment, therapeutic salicylate levels are associated with increases of 50-75% in the unbound fraction of both T(3) and T(4) which persist throughout an 8-10 day treatment period.